Thermodynamic Equilibrium Constants of Mixed Ligand Complexes of Cu(II) with Ethyleneglycol bis (2-aminoethyl ether)-N,N,N´ ,N´ Tetraacetic acid as Primary and Alanine and Phenylalanine as Secondary Ligands - Ahuja, Renu; Dwivedi, K. (Asian Journal of Chemistry, 2010)
Equilibrium studies were carried out potentiometrically for 1: 1 : 1 MAB (A ═ primary and B ═ secondary ligand) systems. Ternary complexation reaction occurs through stepwise equilibria. Thermodynamic equilibrium constants and parameters ΔGº, ΔHº and ΔSº have been calculated.